Classification of Ammonia Odor-profile Using k-NN Technique - Fathimah, Abdul Halim; M. S., Najib; Kamarul Hawari, Ghazali; Muhamad Faruqi, Zahari; Abdul Aziz, Mohd Azoddein (Penerbit UMP, 2016)
This paper presents the application of k-NN in classifying the low and high concentration of ammonia. High concentration of ammonia in water causes serious problematic to water environment and living things in water. Instruments that can directly detect ammonia concentration without any chemical treatment added is limited. Thus, this paper presents detection of ammonia using E-nose and the classification of ammonia in water using k- nearest neighbor (k-NN).